Civil engineering heritage. - Rennison, Robert William, 1930- (Thomas Telford, 1996)
This volume covers Northern England, from the Scottish border to the southern edge of Greater Manchester, Merseyside and South Yorkshire. It is divided into eight geographical areas, mainly based on county boundaries. A site location map and detailed descriptions are given for each site, including an Ordnance Survey grid reference and more.